Mother Teresa - Tames, Richard (New York : F. Watts, 1989)
A biography of the nun who founded the Missionary Sisters and Brothers of Charity and gained wide recognition for her work with the destitute and dying in Calcutta and other places. She was awarded the Nobel Peace Prize in 1979.
Includes index.
Bibliography: p. 30.
Keywords: Teresa, -- Mother, -- 1910- -- Juvenile literature; Teresa, -- Mother, -- 1910-; Missionaries of Charity -- Biography -- Juvenile literature; Missionaries of Charity; Nuns; Missionaries; Women -- Biography; Nobel Prizes -- Biography